2012
DOI: 10.1007/s00396-011-2581-y
|View full text |Cite
|
Sign up to set email alerts
|

Ag nanoparticle-embedded one-dimensional β-CD/PVP composite nanofibers prepared via electrospinning for use in antibacterial material

Abstract: Ag nanoparticle-embedded one-dimensional β-CD (β-cyclodextrin)/PVP composite nanofibers were prepared using a one-step electrospinning technique. Ag nanoparticles were obtained in the AgNO 3 /β-CD/DMF solution, in which silver nitrate been introduced as the precursor, DMF as solvent, β-CD as reducing and capping agent. After electrospinning of the composite solution at room temperature, the β-CD/PVP nanofibers containing Ag nanoparticles were obtained. The electrospun composite solution containning Ag nsnopsrt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…And the result is an agreement with results of the researchers Kaminskiene,et al [14]. As shown in figure (3).…”
Section: 3b Optical Properties Of Addition Ag Nps To Polymer Solutsupporting
confidence: 91%
See 1 more Smart Citation
“…And the result is an agreement with results of the researchers Kaminskiene,et al [14]. As shown in figure (3).…”
Section: 3b Optical Properties Of Addition Ag Nps To Polymer Solutsupporting
confidence: 91%
“…Silver in its dissimilar chemical shapes has been discovered for long time. Silver has large applications such as good antimicrobial agent ,biosensor materials and composite fibers [1][2][3].Silver nanoparticles (AgNPs),in the recent years are extensively studied because of their application as bactericidal substance and other uses of silver nanoparticles (AgNPs) in biomedical field [2]. Also their noticeable antibacterial effectiveness can be credited to the good advanced surface as well as big surface area to size ratio given well contact with the bacteria and microbes [4].Also bacterial cells have strong cytotoxicity as consequence of their contact with the useful collections on the bacterial cell surface [5].Silver nanoparticles can be used in to biosensor materials, antimicrobial applications ,electronic components ,cosmetic and composite fibres [6].The best common technique for creation of stable silver nanoparticles(Ag NPs) is the chemical reduction of Ag ions in dissimilar stabilizers for example polymers.AS in poly(vinylpyrrolidone) where it attracts large care because of its good physical and chemical of its properties creation and its excellent substance as a layer or as an additive to dissimilar materials poly (vinylpyrrolidone) (PVP) performances not just as a steadying agent but too has an influence on the control of the reduction rate of the silver(Ag) ions and aggregation method of Ag [7] 2.…”
Section: Introductionmentioning
confidence: 99%
“…Wang developed silver nanoparticle-embedded one-dimensional β-CD-Poly-Vinyl-Pyrrolidone composite nanofibers using a one-step electrospinning technique. This composite exhibited good antibacterial properties against E. coli and Staphylococcus aureus [125] .…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…Chen and co-workers [33] reported that the stronger antibacterial activity of CTC with the synergistic effect of chitosan, copper, and TiO 2 nanoparticles. Besides the wellknown antimicrobial effect of Ag nanoparticles [8,34], ZnO nanoparticles [12,34], and CuO nanoparticles [35], few Cu 0 nanoparticles were reported.…”
Section: Introductionmentioning
confidence: 98%
“…As a result of its higher specific surface area, metallic nanoparticles have been used in a wide range, including electrode [2], biomedical applications [3], catalyst [4], optical [5], and chemical sensing technologies [6]. Metals such as Ag [7,8], Au [9], Al [10], Pd [11], and Zn [12] have been added into the structures of nanoparticles. However, compared with these metallic nanoparticles, Cu nanoparticles are specifically focused on because they offer low processing costs, high conductivity, and high catalytic activity [13].…”
Section: Introductionmentioning
confidence: 99%